Caracterização de usuários no Instagram - Oliveira, Rodrigo Ribeiro (2021)
With the popularization of social media, more and more data is created, generating new opportunities of extracting knowledge from it. An example of social media that became popular in recent years is Instagram, whose focus is image sharing. For marketing purposes, the characterization of users is a very important task, because it allows to deliver specific advertisements for each group of users. This approach allows for applications in marketing, pointing to users within an intended demography. This problem is tackled in this work, in particular, the determination of age range and professional area in Instagram users that are native speakers of Portuguese. Two datasets of Instagram profiles were built, one labeled with the age range and another with the professional area of the users. The classifiers Random Forest and Support Vector Machines were used for determining these characteristics, through textual and behavioral attributes. The best results achieved have a accuracy of 60%, performance superior to the baseline for each problem.